P53-induced reduction of lipid peroxidation supports brain microvascular endothelium integrity - Mohammad S. Akhter; Mohammad A. Uddin; Khadeja-Tul Kubra; Nektarios Barabutis (Elsevier, 2019)
Dysregulation of the blood brain barrier due to oxidative stress causes neurological disorders, such as Alzheimer's and Parkinson's disease. We employed brain microvascular endothelial cells; to investigate the effects of P53 towards the lipid oxidation of the BBB. P53 reduction by LPS, siRNA for P53 and Pifithrin increased the expression levels of malondialdehyde, a marker of oxidative stress and lipid peroxidation. Furthermore, P53 suppression impaired the permeability of the BBB monolayers. In contrast, P53 induction by Nutlin and Hsp90 inhibitor AUY922 enhanced the BBB function. In conclusion, P53 supports BBB integrity, at least in part, by reducing lipid peroxidation. Keywords: Cerebral stroke, Inflammation, Barrier function